Do anxious swimmers swim slower? - Burton, D. (Journal of Sport & Exercise Psychology, 1988)
Cognitive anxiety is the mental component of anxiety caused by negative expectations about success or negative self-evaluation (e.g., worry, negative self-talk, and unpleasant imagery). Somatic anxiety is the physiological or affective component of anxiety that is directly related to autonomic/physiological arousal (e.g., what the athlete feels -- rapid heart rate, butterflies in the stomach, tense muscles). Sample 1 comprised male (N = 15) and female (N = 13) collegiate swimmers. Each swimmer completed the Competitive Sport Anxiety Inventory -- 2 (CSAI-2) prior to an early season invitational meet, a mid-season conference dual meet, and the Big Ten Conference championships. Sample 2 was composed of male (N = 31) and female (N = 39) serious swimmers who competed at the National Sports Fesitval (average age 17.4 yr). The CSAI-2 was completed once after practice two days before competition and again within one hour of the most important race at the meet. Anxious swimmers generally perform slower times. The cognitive component of anxiety showed a stronger relationship to performance decline than the somatic component. However, the somatic-anxiety to performance relationship was found to be different between sprint and distance swimmers. Better-performing sprinters tended to control their somatic anxiety better than poorer performers. In distance events, better performers tended to attain higher levels of physiological arousal than poorer performers. Implication: It is important that swimmers approach competitions with confidence and a positive mind-set. Any negative talk is likely to indicate the swimmer has a strong likelihood of performing below expectations. For distance events it is important to "get up" for a race to mobilize sufficient energy to maintain a strong pace. However, sprinters must remain controlled with an optimum level of physiological arousal. The mental state of pre-race preparations is more important than the physical state that is attained. It is imperative that swimmers remain mentally controlled during the pre-race period.